THE EFFECT OF USING CABRI 3DV2PLUS SOFTWARE WITH COOPERATIVE INTERACTION SETTING LEARNING MODEL ON STUDENTS' MATHEMATICAL UNDERSTANDING IN TRANSFORMATION MATERIALS - Batubara, Nur Asiah; Roza, Yenita; Yuanita, Putri (International Journal of Educational Best Practices, 2019)
This study is aimed at identifying the effect of using Cabri 3DV2Plus software with a learning model of cooperative interaction settings of students who get conventional learning seen from the level of students' abilities (high, medium, or low). The research uses a quasi-experimental method. The population in this study were students of class XI. The sampling technique was done by random sampling, and a sample of 182 students was obtained. The instrument used in this study was a test of mathematical understanding. The data collection techniques for mathematical understanding were carried out by giving a pretest and a posttest. The statistical analysis carried out was a normality test and a homogeneity test as a condition for taking the treatments, and a t-test to see the average difference in each class. From the t-test, the tcount and ttable values were obtained respectively. tcount1 =11.20 ≥ ttable = 2.042, tcount2 =9.819 ≥ ttable = 2.042, and tcount3 = 4.861≥ ttable = 2.042 then overall H0 is rejected; meaning that there is influence of using Cabri 3DV2Plus software with the learning model of cooperative interaction settings of students who get conventional learning in terms of the level of students' ability (high, medium, or low).